Results of Onomastics in Geolinguistics: Expedition Experience - Mickienė, Ilona; Baranauskienė, Rita (Respectus Philologicus, 2012)
This paper summarises the research material of the ongoing global grant project, “Modern Research of Geolinguistics in Lithuania: Optimisation of Network of Points and Interactive Spread of Dialectal Information.” The project aims to collect the most important sociolinguistic data of the entire Lithuanian language area, with the purpose of carrying out a primary analysis of the items found in order to make a record of the Lithuanian language situation at the beginning of the 21st century.In fact, the collecting of toponyms started earlier, especially after the foundation of the Group of Onomastics at the Lithuanian Academy of Sciences, at the Institute of the Lithuanian Language and Literature in 1958. In the period of 1976–1986, the Institute, in collaboration with the Society of Heritage Protection and Regional Studies, launched 11 major expeditions to several regions of Lithuania. Expeditions on onomastics and dialectology were also organised at the Vilnius University Kaunas Faculty of Humanities. In the period of 1979–1989, students of the Kaunas Faculty of Humanities, supervised by Albertas Ružė, collected the onyms in the Samogitian region (Telšiai, Mažeikiai, Akmenė and two-thirds of the Skuodas district). During the abovementioned period, two two-day long annual expeditions to the birthplaces of outstanding Lithuanian linguists (e.g., Juozas Balčikonis, Jonas Kazlauskas and others) were organised. In 1977–1988, the expedition members, under the direction of Alvydas Butkus, collected the onyms in such areas as Ukmergė, Molėtai, Utena, Kaunas, Pasvalys, Biržai, Jurbarkas, and Lazdijai.The paper overviews one aspect of the item questionnaire, i.e., the onomastics of part of the live language heritage: toponyms and nicknames. The research is based on the descriptive method and deals with the analysis of the toponyms and nicknames of the dialectal items of the Pasvalys, Kaunas and Marijampolė counties. Moreover, it gives an explanation of the folk etymology of the item names. The research involved 87 informants (of both genders) from different dialect areas and of different generations – the younger (under 30 years old), the middle (31–49 years old), and the elder (50 years old and over). Due to the rather fresh start of the project, the current paper presents only some initial insights, which will be revised upon the completion of the project.
Keywords: onomastics; toponyms; nicknames; folk etymology